2020
DOI: 10.5539/ies.v14n1p40
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Analysis of the Status Quo of Normal University Students’ Teaching Internship——Taking Taishan University as an Example

Abstract: Teaching internship is an effective form of cooperation between university and primary and middle school. Teaching internship can promote the improvement of the teaching quality of internship primary and secondary schools, and also promote the integration of theoretical knowledge and practical experience by college students, and promote the professional development of college students. In order to grasp the situation pertaining to normal students’ teaching internship, we conducted a questionnaire sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It can be concluded that the shape of the Silat sub-watershed basin is narrow. Therefore, the flood confluence time is short for a narrow basin (Liu, 2011). Therefore, the small basin circularity ratio of the Silat River supports the formation of a high flood peak, which easily drains large amounts of runoff from the basin during rainy days to the Silat Sub Watershed.…”
Section: Shape Of Sub Watershedmentioning
confidence: 99%
“…It can be concluded that the shape of the Silat sub-watershed basin is narrow. Therefore, the flood confluence time is short for a narrow basin (Liu, 2011). Therefore, the small basin circularity ratio of the Silat River supports the formation of a high flood peak, which easily drains large amounts of runoff from the basin during rainy days to the Silat Sub Watershed.…”
Section: Shape Of Sub Watershedmentioning
confidence: 99%
“…This activity assists them in knowing how to encourage their social relationship or work partnership (Maertz et al, 2014). Further, Liu (2020) explained that interns have to deal with a bunch of work, and sometimes they do not have much time to discuss the topic of the lesson in their teaching activities. To overcome this challenge, it is very crucial to build communication with supervisors to discuss and find the solution together.…”
Section: Communicating With Supervisormentioning
confidence: 99%
“…AMOS 21.0 is used to analyze 302 QSs collected. The evaluation criteria and fitting results of the model fitting degree are shown in Figures 9 , 10 (Abebe, 2019 ; Atitsogbe et al, 2019 ; Abulela and Davenport, 2020 ; Liu, 2021 ).…”
Section: Reliability Evaluation and Analysis Of Innovation And Entrepreneurship Education Classroom Teachingmentioning
confidence: 99%